Trade and environment governance at the World Trade Organization Committee on Trade and Environment - Teehankee, Manuel A. J. (Global trade law series ;, 2020)
"Trade and Environment Governance at the World Trade Organization Committee on Trade and Environment" focuses on resolving the conflict between environment and trade norms through dispute settlement mechanisms. The author of this book has interacted as an ambassador with negotiators, such as the World Trade Organization (WTO)Secretariat, media, and academics. This book has very little competition as it is one of the first of its kind to have systematically analyzed WTO?s Committee on Trade and Environment (CTE) in great depth and designed environmentally friendly trade policies by taking into consideration the perspectives of the developing-developed economies. It aims to demonstrate that increased knowledge and experience-sharing plus coordination among international and local experts and the professional bureaucracy are key to formulating practical approaches to new rules in the areas of trade and environment governance and minimizing potential policy conflicts.